Code Switching And Code Mixing Found In The Shallow Stuff's Utterance - Putri, Kadek Rina Desiyana; Utami, Ni Made Verayanti; Ariyaningsih, Ni Nyoman Deni (Lingual Journal of Language and Culture, 2022)
This study aims to determine the types and functions of code switching and code mixing between Indonesian and English that occur in the utterance made by one of Indonesia's beauty vlogger, Shallow Stuff in three videos from her YouTube channel. The analysis is using there different theories, a theory proposed by Poplack in Romaine (1995) to analyze the types of code switching, the second theory is proposed by Muysken (2000) to analyze the types of code mixing, and a theory proposed by Marasigan (1983) to analyze the functions of code switching and code mixing. The direct observation method is used by transcribing and note-taking the utterance that contains code switching and code mixing from the video. The results indicate that the most frequent code switching in Shallow Stuff's utterance is intra-sentential switching because she often switches her utterance using English sentences, on the other hand, the result found the most frequent code mixing is the insertion. Keywords: code switching, code mixing, beauty vlogger